Morfologi, Hasil, dan Korelasi Organ Vegetatif dan Generatif Tanaman Kedelai Varietas Wilis di Tanah Masam pada Musim Hujan: Morfologi, Hasil, dan Korelasi Organ Vegetatif dan Generatif Tanaman Kedelai Varietas Wilis di Tanah Masam pada Musim Hujan - M. Umar Harun; Chandra Irsan; Haris Kriswantoro (Universitas Bangka Belitung, 2022)
Soybean poorly performed if planted during dry season. Planting during the rainy season can overcome problem of limited water availability. This study examines the response of soybean to rainy season in acid dry land. Research was then conducted at Timbangan village, Ogan Ilir, South Sumatra from October 2020 through January 2021. Soybean seeds of Wilis variety as planting material were already one month old. The research was carried out without applying experimental design. Five plots were prepared with each size 4 m x 2.5 m, and planted in 6 rows. Soil was prepared by thoroughly mixing with dolomite (2 tons ha-1), chicken manure 10 tons ha-1, and Urea (50 kg ha-1), SP 36 (100 kg ha-1), and KCl (50 kg ha-1). Sampling of plants by purposive sampling. The variables measured were plant height, number of leaves, number of branches, number of filled pods, weight of seeds per plant, dry weight of pods, stems, leaves, and roots. Finding of the research, plant height (68.5±5.45 cm) and weight of 100 seeds per plant (13.19±3.27 g) was above description. Correlation-regression test showed that root dry weight had a significantly positive correlation to stems and branch numbers, leaf dry weight and pod dry weight.